EFEKTIVITAS PROGRAM MAGANG PRAKTIK INDUSTRI: TINJAUAN DARI PERSPEKTIF MAHASISWA PENDIDIKAN VOKASIONAL SENI KULINER UMS RAPPANG - Samratusabri Subehan; Suhartini Khalik; Yusrianti; Yayuk Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study assesses the effectiveness of the industrial practice internship program for UMS Rappang Culinary Arts Vocational Education students using a mixed-method approach involving questionnaires, open-ended responses, and analysis of final internship reports. Findings show the program is effective to very effective,particularly in technical skills, work readiness, and the relevance of theory topractice. Qualitative data highlight meaningful experiences consistent with Kolb’s(1984) experiential learning stages and Schermerhorn & Bachrach’s (2023)organizational effectiveness theory. Secondary data support these results,indicating growth in skills, teamwork, and innovation. Recommendations includeimproving pre-internship preparation, strengthening mentoring, and enhancingcampus–industry collaboration.